Biologically Guided Optimization of Test Target Location for Rod-mediated Dark Adaptation in Age-related Macular Degeneration - Cynthia Owsley, PhD, MSPH; Thomas A. Swain, MPH; Gerald McGwin, Jr., PhD, MS; Mark E. Clark, MEng; Deepayan Kar, MS; Christine A. Curcio, PhD (Ophthalmology Science, 2023)
Purpose: We evaluate the impact of test target location in assessing rod-mediated dark adaptation (RMDA) along the transition from normal aging to intermediate age-related macular degeneration (AMD). We consider whether RMDA slows because the test locations are near mechanisms leading to or resulting from high-risk extracellular deposits. Soft drusen cluster under the fovea and extend to the inner ring of the ETDRS grid where rods are sparse. Subretinal drusenoid deposits (SDDs) appear first in the outer superior subfield of the ETDRS grid where rod photoreceptors are maximal and spread toward the fovea without covering it. Design: Cross-sectional. Participants: Adults ≥ 60 years with normal older maculas, early AMD, or intermediate AMD as defined by the Age-Related Eye Disease Study (AREDS) 9-step and Beckman grading systems. Methods: In 1 eye per participant, RMDA was assessed at 5° and at 12° in the superior retina. Subretinal drusenoid deposit presence was identified with multi-modal imaging. Main Outcome Measures: Rod intercept time (RIT) as a measure of RMDA rate at 5° and 12°. Results: In 438 eyes of 438 persons, RIT was significantly longer (i.e., RMDA is slower) at 5° than at 12° for each AMD severity group. Differences among groups were bigger at 5° than at 12°. At 5°, SDD presence was associated with longer RIT as compared to SDD absence at early and intermediate AMD but not in normal eyes. At 12°, SDD presence was associated with longer RIT in intermediate AMD only, and not in normal or early AMD eyes. Findings were similar in eyes stratified by AREDS 9-step and Beckman systems. Conclusions: We probed RMDA in relation to current models of deposit-driven AMD progression organized around photoreceptor topography. In eyes with SDD, slowed RMDA occurs at 5° where these deposits typically do not appear until later in AMD. Even in eyes lacking detectable SDD, RMDA at 5° is slower than at 12°. The effect at 5° may be attributed to mechanisms associated with the accumulation of soft drusen and precursors under the macula lutea throughout adulthood. These data will facilitate the design of efficient clinical trials for interventions that aim to delay AMD progression. Financial Disclosure(s): Proprietary or commercial disclosure may be found after the references.